2001
DOI: 10.1002/jat.782
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective role of angiotensin‐converting enzyme inhibitors captopril and enalapril against adriamycin‐induced acute cardiac and hepatic toxicity in rats

Abstract: Captopril and enalapril-angiotensin-converting enzyme (ACE) inhibitors-were evaluated for their antioxidative protective action against adriamycin-induced cardiac and hepatic toxicity. Rats were treated with either captopril (10 mg kg(-1)) or enalapril (2 mg kg(-1)) intragastrically (i.g.) daily for 7 days before single intraperitoneal (i.p.) injection with adriamycin (15 mg kg(-1)). The animals were killed 30 h after adriamycin administration. Adriamycin produced significant elevation in thiobarbituric acid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 41 publications
6
50
0
1
Order By: Relevance
“…In several studies, both sulfydryland non-sulfydryl-containing ACEIs have been shown to be effective free radical scavengers, having an antioxidant effect on adriamycin-induced cardiotoxicity. 18,33 The mechanism by which enalapril prevents the development of cardiotoxicity remains uncertain. Hemodynamic abnormalities and systemic activation of RAS probably were not present in our population, given the normal LVEF observed at the time of patient randomization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, both sulfydryland non-sulfydryl-containing ACEIs have been shown to be effective free radical scavengers, having an antioxidant effect on adriamycin-induced cardiotoxicity. 18,33 The mechanism by which enalapril prevents the development of cardiotoxicity remains uncertain. Hemodynamic abnormalities and systemic activation of RAS probably were not present in our population, given the normal LVEF observed at the time of patient randomization.…”
Section: Discussionmentioning
confidence: 99%
“…9 -12 Furthermore, data referring to experimental models suggest that the cardiac renin-angiotensin system (RAS) plays an important role in the development of anthracycline-induced cardiomyopathy and that treatment with ACEIs protects against chemotherapy-induced cardiotoxicity. [13][14][15][16][17][18][19] Hence, it is likely that a prophylactic strategy based on the use of ACEIs in selected high-risk patients could prevent cardiotoxicity.…”
Section: Editorial P 2432 Clinical Perspective P 2481mentioning
confidence: 99%
“…Furthermore, the treatment significantly affected the proteome lysine acetylation status in the heart, inducing deacetylation (Figure 1), although the significance of this observation is currently unknown. Because previously published studies have reported that acute Dox treatment does affect many of these variables and processes [8][9][10][11][35][36][37] , we believe that complete fasting of the animals in our study may have exerted an unintended cardioprotective effect against the Dox-induced insult. However, further investigation is required to confirm our interpretation of the data.…”
Section: Dox-induced Cardiotoxicitymentioning
confidence: 88%
“…Inflammation is a major component in the pathogenesis of DOX toxicity that is orchestrated in part by endogenous and migrating leukocytes. Abd El-Aziz et al (2001) demonstrated that a 15 mg/kg single injection of DOX caused increased lipid peroxidation and produced reactive oxygen species in liver tissue, thus reduced the antioxidant defence mechanism. Dilatation of the blood sinusoids and degeneration may be due to this stress.…”
Section: Discussionmentioning
confidence: 99%